Liver Function Profile of Pediatric Patients with Dengue Viral Infection Admitted to a Tertiary Referral Hospital during the COVID-19 Pandemic - Rosalina, Ina; Adrizain, Riyadi; Sari, Chindy Arya; Alam, Anggraini; Setiabudi, Djatnika (Althea Medical Journal, 2023)
Background: Dengue infection is endemic in more than 100 countries; 70% of cases occur in Asia. One of dengue infection complication is hepatic dysfunction. The COVID-19 pandemic may cause a delay in seeking treatment and affect severe case of dengue infection when admitted to the hospital. This study aimed to analyze the liver function profile in dengue pediatric patients during the COVID-19 pandemic.Methods: All patients under 18 with confirmed dengue serology (NS-1 immunochromatography or IgM anti-Dengue (ELISA) test and IgG anti-Dengue (ELISA) test) in Dr. Hasan Sadikin General Hospital from 2021–2022 were included in this retrospective study. The patients were categorized based on the modified WHO classification of 2009. Data were processed with SPSS® ver. 25 and analyzed using Chi-Square and One Way-ANOVA.Result: In total, 85 patients were tested for the liver function; most severe dengue patients had abnormal SGOT and SGPT levels (100% vs. 64%).  The SGOT and SGPT levels during the initial admission were higher in the severe dengue group (634 U/l and 271 U/l) and significantly different among groups (p=0.001 and p=0.032). The elevated SGOT (1,339 U/l vs. 203 U/l vs. 87.3 U/l; p=0.014) and SGPT (438 U/l vs. 100 U/l vs. 42.8 U/l; p=0.005) levels were higher in the severe dengue group.Conclusion: The severity of dengue is in line with the increase in SGOT and SGPT levels. During the COVID-19 pandemic, the liver dysfunction persists and may be interfered with by delays in dengue treatment. Early recognition and prompt treatment are needed to decrease morbidity and mortality.